Energy Harvesting Wireless Sensor Network (Eh-Wsn) Based Modified Negatively Correlated Search Algorithm For Non-Convex Optimization Problems - et. al., Maddali M.V.M. Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Network resource allotment is a significant concern for designing energy harvesting wireless sensor networks (EHWSNs). So, in this manuscript, Modified Negatively Correlated Search by Harris Hawks Optimization (MNCSHHO) algorithm is proposed for EH-WSNs with interference channel to solve the Non convex problems. It also used for optimizing data rates, energy transfers, and minimizing the total network delay. Initially, it deals with the complicated nonlinear constraints and also optimizes the data rates and energy transfer. By this total network delay can be minimized. The simulations are performed using Network Simulator (NS2) to validate the performance of the proposed Modified Negatively Correlated Search by Harris Hawks Optimization (MNCSHHO) algorithm and it provide better results such as high network life time as 1.09, 2.34, high throughput as 0.65, 1.024, energy transfer as 24%, 51%, low delay as 20.29%, 42.416%, low drop as 2.34%, 3.3455% and low overhead as 40.52%, 23.4% are compared with the existing algorithms like EDS-NCS, convex approximation respectively.